Pedagogical Education as the Development of Initial Pedagogical Ideas - A.A. Margolis (Психологическая наука и образование)
The article examines the role of initial pedagogical beliefs held by students in teacher training programs as they begin to engage with pedagogical education curricula. It highlights the significance of school experiences in shaping these beliefs. The article analyzes the reasons for their sustainability during the subsequent acquisition of the educational program by future educators at the university level. The author argues for the necessity of designing teacher training programs in the form of a sequential and specially organized transformation of initial pedagogical beliefs, aimed at fostering conceptual change and developing the practical thinking of future educators.